2017
DOI: 10.1111/jocd.12387
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dermatologic manifestations and metabolic biomarkers in women with polycystic ovary syndrome in north China

Abstract: This study indicated a strong correlation between hirsutism and metabolic abnormalities. Hirsutism is the most common cutaneous finding in PCOS women. Acne and AGA are associated with other manifestations of clinical hyperandrogenism, but not obvious markers of biochemical hyperandrogenemia and metabolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
5
20
1
3
Order By: Relevance
“…There was also a very high prevalence of hirsutism among PCOS patients (93%; 125/134). Such finding is in good agreement with previous studies that have reported high prevalence of hirsutism in PCOS women estimating 28% [38], 62.5% [35] and 58.1% [40], which further supports that hirsutism is the most common skin manifestation in PCOS [33]. The higher prevalence found in our finding might be attributed to the fact that all our patients were evaluated after properly diagnosed to have PCOS.…”
Section: Discussionsupporting
confidence: 93%
“…There was also a very high prevalence of hirsutism among PCOS patients (93%; 125/134). Such finding is in good agreement with previous studies that have reported high prevalence of hirsutism in PCOS women estimating 28% [38], 62.5% [35] and 58.1% [40], which further supports that hirsutism is the most common skin manifestation in PCOS [33]. The higher prevalence found in our finding might be attributed to the fact that all our patients were evaluated after properly diagnosed to have PCOS.…”
Section: Discussionsupporting
confidence: 93%
“…7,9,10 In this study, 28% of the patients were overweight and 24% were obese while in study by Ramanand Among cutaneous manifestations of PCOS, hirsutism was the most common finding occurring in 85% patients similar to study by Keen et al and Jain et al 7,8 In contrast studies by Gowri et al, Hong et al, Fang et al showed acne to be the most common manifestation. 2,11,12 Mukkamala et al, found acanthosis nigricans as the most common presentation in cases of PCOS. 9 The most common hormonal abnormality in this study was insulin resistance in 53% patients, followed by raised free testosterone in 19% patients whereas in study by Gowri et al, raised testosterone levels in 55% patients was the most common manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…China is a large and multi-ethnic country with many provinces that include cities and rural areas. Therefore, the occurrence and clinical manifestations of PCOS in different ethnic groups in China are also different [ 15 , 16 ]. There are a large number of ethnic minorities with different living habits in Xinjiang Province, which includes the Uygur and Han ethnic groups.…”
Section: Introductionmentioning
confidence: 99%